Infant Outcomes of HIV Positive Mothers Based on HIV PCR Test Result at Jayapura District Hospital - James Thimoty; Kurnia Sari (Postgraduate, University of Mataram, 2025)
Mother Mother-to-child transmission (MTCT) is the primary route of HIV infection in children under 14 years. Despite the expansion of prevention of mother-to-child transmission (PMTCT) programs and increased antiretroviral therapy (ART) coverage, 17,000 children aged 0–14 years were living with HIV in Indonesia in 2023. This retrospective study analyzed infants born to HIV-positive mothers between January 2018 and December 2022, including only those with HIV polymerase chain reaction (PCR) test results. Of 86 infants, 21 (24.4%) tested positive for HIV, while 65 (75.6%) tested negative. Among those with positive results, 76.2% had an APGAR score <7, 90.5% were term, and 85.7% had a birth weight of ≥2500 grams. All infants received ART prophylaxis, and 91.9% were formula-fed. Infants whose mothers did not receive ART before birth or during labor had a 15-fold higher risk of HIV infection. Additionally, discontinuation of ART prophylaxis before six weeks of age increased the risk fourfold. These findings highlight the importance of early detection of HIV in pregnant women, optimising ART adherence during pregnancy, and providing ART prophylaxis to infants to reduce HIV transmission. Strengthening prevention of mother-to-child transmission (PMTCT) programmes is needed to reduce infant HIV cases in high-prevalence areas such as Papua.